If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y = 3x + -23 Reorder the terms: 7y = -23 + 3x Solving 7y = -23 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '7'. y = -3.285714286 + 0.4285714286x Simplifying y = -3.285714286 + 0.4285714286x
| (4-2x)=24 | | 5p^2-34+24= | | 8/9+i=0 | | g(x)=8 | | g(6)=8 | | 6y-12=5y-10 | | -3-(8x-4)=3(x+2)+7 | | -14x+7=21 | | -x-2(x+1)=1-7x | | 3(2x+8)=2(2x+40) | | 10x-7y=44 | | 5+2(x+3)=-x-6 | | 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 |